Dynamics of Rural Growth in Bangladesh : Sustaining Poverty Reduction - Gautam, Madhur; Faruqee, Rashid (Washington, DC: World Bank, 2016)
The rural economy in Bangladesh has powerfully advanced economic growth and substantially reduced poverty, especially since 2000, but the remarkable transformation and unprecedented dynamism in rural Bangladesh remain an underexplored, underappreciated, and largely untold story. Dynamics of Rural Growth in Bangladesh: Sustaining Poverty Reduction tells that story and inquires what specific actions Bangladesh might take—given the residual poverty and persistent malnutrition—to accelerate and channel its rural dynamism to sustain the gains in eliminating poverty, achieving shared prosperity, and advancing national aspirations to achieve middle-income status.